Development of Method for Discontinuing Mercury-Containing Waste Including the Method of Analysis of Residual Concentrations - Makarova, Anna; Fedoseev, Andrew; Kushu, Anastasia; Vinokurov, Eugene (KnE Materials Science, 2020)
Environmental safety is one of the most important international and national tasks when using chemicals such as mercury, its compounds and mercury containing waste. Mercury (Hg) is a global pollutant. Constant anthropogenic mercury emissions and its presence in food chains affects human and ecosystem health and cause serious concerns. When released into the atmosphere with various emissions, mercury is deposited on the ground or water surface. Due to the global transport of mercury in the environment, its release is possible near sources of pollution, as well as at a remote distance. Keywords: mercury–containing wastes, Minamata Convention, immobilization